2021
DOI: 10.1007/s11356-021-15435-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Nb2O5 nanofibers in photocatalytic degradation of organic pollutants

Abstract: Due to the pollution caused by different organic pollutants, various photocatalytic nanomaterials for environmental remediation have been promoted. In this study, Nb 2 O 5 nano bers were obtained by electrospinning technique, presenting controlled crystallinity and high speci c surface area to improve the photoactivity response. The structural characterization indicated Nb 2 O 5 nano bres with orthorhombic phase formation, and the photoluminescence measurements showed different energy levels contributing to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 65 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Recent literature [18,19] has focused on producing niobium-based fibers for photodegradation of the organic pollutants, using polyvinylpyrrolidone (PVP) as a polymeric precursor. The results indicate that the pseudohexagonal TT-Nb 2 O 5 phase showed greater efficiency, more than 62% degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature [18,19] has focused on producing niobium-based fibers for photodegradation of the organic pollutants, using polyvinylpyrrolidone (PVP) as a polymeric precursor. The results indicate that the pseudohexagonal TT-Nb 2 O 5 phase showed greater efficiency, more than 62% degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that TC has p K a1 = 3 and p K a2 = 9, suggesting that TC presents in the form of zwitterions at 3 < pH < 9 . At pH = 7, both surface charges of PAA and Bi-N-CDs/BiOBr are negative (Figure S6); hence, electrostatic repulsion may be the main interaction between Bi-N-CDs/BiOBr@TW and zwitterionic TC and RhB, thus restraining the removal of contaminants. ,, Nevertheless, positively charged CV (p K a = 9.4) and MB (cationic) are readily absorbed onto Bi-N-CDs/BiOBr@TW because of electrostatic attraction, thus facilitating elimination reactions. , Impressively, the lower removal efficiency of MB compared to CV may be caused by the weak photosensitivity of MB due to its maximum absorption at 664 nm (Figure S7). TC, as an achromatic molecule, shows only 46.3% removal rate after 300 min, which is due to the absence of a photosensitization process, so it is not susceptible to photodegradation .…”
Section: Resultsmentioning
confidence: 99%
“…39,40,45 Nevertheless, positively charged CV (pK a = 9.4) and MB (cationic) are readily absorbed onto Bi-N-CDs/BiOBr@TW because of electrostatic attraction, thus facilitating elimination reactions. 46,47 Impressively, the lower removal efficiency of MB compared to CV may be caused by the weak photosensitivity of MB due to its maximum absorption at 664 nm (Figure S7). TC, as an achromatic molecule, shows only 46.3% removal rate after 300 min, which is due to the absence of a photosensitization process, so it is not susceptible to photodegradation.…”
Section: Optical Transmittance Of Wood Hydrogelsmentioning
confidence: 99%
“…In the present case, we cannot assure that this was the cause of the formation of a mixture of crystalline T‐Nb 2 O 5 and H‐Nb 2 O 5 . Nevertheless, several studies connect the presence of T‐Nb 2 O 5 to an increase in photocatalytic activity, depicting results for RhB, [ 59 ] methyl blue (MB), [ 58 ] methyl orange (MO), [ 64 ] and fluoxetine (FLX) [ 65 ] above 40% of the photodegradation.…”
Section: Resultsmentioning
confidence: 99%